DMT and harmala alkaloids: an exploratory study of oral Acacia based formulations in healthy volunteers - Yvonne A. Bonomo; Yvonne A. Bonomo; Amanda F. Norman; Lisa Collins; Margaret Ross; Justin Dwyer; Daniel Perkins; Daniel Perkins; Daniel Perkins; Jerome Sarris; Jerome Sarris; Jerome Sarris; et al. (Frontiers in Psychiatry)
IntroductionAyahuasca is a psychedelic compound of N, N, Dimethyltryptamine (DMT) and harmala alkaloids used for spiritual and medicinal applications in traditional settings. A range of potential psychotherapeutic mechanisms have been proposed for ayahuasca. These are thought to contribute to improvements in various psychiatric conditions including mood disorders and substance dependence. This open label exploratory study explored safety, tolerability, physical, mental health and psychedelic effects of three Acacia based formulations in 9 healthy volunteers with prior use of Ayahuasca.MethodFormulations derived from two Acacia species (1mg/kg DMT and 4mg/kg of harmalas) were tested in a cross-over design in 5 adults; a third formulation (ACL-010) was tested in 4 adults at two dosages (1mg/kg DMT and 4mg/kg of harmalas, and then 1.4mg/kg DMT and 5.6mg of harmalas).ResultsAll formulations had a good safety profile. No serious adverse events were reported. Physical examination, vital signs, and pathology revealed no clinically significant changes across the course of the study. The subjective experience of all formulations was generally rated similar to Ayahuasca. Four-week follow-up measures of psychological wellbeing and perceptual effects showed little difference between formulations. The strength and quality of the psychedelic experience elicited with ACL-010 was rated as similar or more beneficial than Ayahuasca.DiscussionOur results indicate DMT formulations derived from the Acacia species represent a feasible alternative to traditional Ayahuasca for future clinical trials and possibly clinical contexts. The small sample size and open label design limit generalizability of results.Clinical trial registrationhttps://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=384191&isReview=true, identifier ACTRN12622001315707.